Age group and individual differences in attentional orienting dissociate neural mechanisms of encoding and maintenance in visual STM. - Shimi, A; Kuo, B; Astle, D; Nobre, A; Scerif, G (2014)
Selective attention biases the encoding and maintenance of representations in visual STM (VSTM). However, precise attentional mechanisms gating encoding and maintenance in VSTM and across development remain less well understood. We recorded EEG while adults and 10-year-olds used cues to guide attention before encoding or while maintaining items in VSTM. Known neural markers of spatial orienting to incoming percepts, that is, Early Directing Attention Negativity, Anterior Directing Attention Negativity, and Late Directing Attention Positivity, were examined in the context of orienting within VSTM. Adults elicited a set of neural markers that were broadly similar in preparation for encoding and during maintenance. In contrast, in children these processes dissociated. Furthermore, in children, individual differences in the amplitude of neural markers of prospective orienting related to individual differences in VSTM capacity, suggesting that children with high capacity are more efficient at selecting information for encoding into VSTM. Finally, retrospective, but not prospective, orienting in both age groups elicited the well-known marker of visual search (N2pc), indicating the recruitment of additional neural circuits when orienting during maintenance. Developmental and individual differences differentiate seemingly similar processes of orienting to perceptually available representations and to representations held in VSTM.